From Tweets to Thrills: The Evolution of Digital Storytelling on YouTube through Nessie Judge's Horror Narratives - Diego, Diego; Lestari , Yayuk; Sarmiati, Sarmiati (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
This research investigates the widespread and even impact phenomenon generated by the audience's enthusiasm for YouTube content presented by Nessie Judge. Nessie Judge's unique narrative style has successfully sparked strong enthusiasm among YouTube subscribers, who eagerly await each episode of her content with excitement. This study holds significant significance as it examines Nessie's storytelling ability, often supported by compelling evidence and presented from a deep perspective. The horror genre in the story